Proposal to Update the Curriculum in Inflammatory Bowel Diseases for Categorical Gastroenterology Fellows. Issue 9 (22nd May 2019) - Malter, Lisa B; Israel, Amanda; Rubin, David T
Abstract: Education in inflammatory bowel disease (IBD) varies widely between categorical gastroenterology (GI) programs and is largely related to the presence of expert clinicians, patient population, and the presence of an IBD center. The treatment of IBD is becoming increasingly complex at a rapid pace, widening this educational divide. This manuscript outlines all the current US educational offerings in IBD for GI fellows, including how to obtain supplemental education during the 3-year training period and beyond. It reviews how to assess trainee knowledge in the field of IBD and proposes 8 clinically anchored, entrustable professional activities that should help prioritize important aspects of IBD management to incorporate during categorical GI training. Abstract : This manuscript outlines the current state of training in IBD for categorical GI fellows, which varies widely. All supplemental IBD educational offerings are reviewed, and we propose a list of IBD entrustable professional activities to help prioritize teaching this topic. Video Abstract: